Infant and young child feeding : current issues - World Health Organization (Geneva : WHO, 1981)
ãAĉa This document is based on the background paper prepared for the joint WHO/UNICEF on the promotion of breastfeeding and improvement of i nfant and young child nutrition.
Includes bibliographical references.
Keywords: Breast Feeding; Lactation; Infant Nutrition; Nutrition; Pregnancy